2017
DOI: 10.3920/bm2016.0231
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of a probiotic blend on gastrointestinal side effects induced by leflunomide and amlodipine in a rat model

Abstract: Patients with metabolic disorders frequently suffer from side effects induced by long-term oral medications. The present study using a rat model system indicated that leflunomide (LF) and amlodipine (AMD), the active ingredients contained in the medications for rheumatoid arthritis and hypertension, respectively, appeared to induce various bowel problems including constipation and inflammation. In the small and large intestine, LF increased the expression of tumour necrosis factor (TNF)-α, interleukin (IL)-1β,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…As shown in Figure 1, the control group and the AMD group were clearly divided into two clusters on the PCA score plot, whereas the AMD+PB group displayed a pattern almost identical to that of the control group. This result is in good agreement with the previous finding that the PB alleviated intestinal complications caused by AMD [19].…”
Section: Statistical Analysis Of the Serum Metabolomesupporting
confidence: 93%
See 2 more Smart Citations
“…As shown in Figure 1, the control group and the AMD group were clearly divided into two clusters on the PCA score plot, whereas the AMD+PB group displayed a pattern almost identical to that of the control group. This result is in good agreement with the previous finding that the PB alleviated intestinal complications caused by AMD [19].…”
Section: Statistical Analysis Of the Serum Metabolomesupporting
confidence: 93%
“…The probiotic blend used in this study was previously shown to have beneficial effects on human subjects with irritable bowel syndrome [45] and on animals with indomethacin-induced small intestine injury [46]. In our previous experiment, it was found to bring down increased levels of inflammatory cytokines in AMD-administered rats [19]. Glucocorticoids, including corticosterone in rodents and cortisol in humans, are anti-inflammatory steroid hormones [47,48].…”
Section: Identification and Comparison Of Corticosterone And Adrenocomentioning
confidence: 82%
See 1 more Smart Citation
“…This could be explained because in this previous study, a great part of HT patients had taken antihypertensive drugs and they were in a more advance hypertension grade. It has been recently reported that the hypertensive drug treatment can induce compositional changes in the gut microbiota and also inflammation 24 , so drug-induced gut microbiome shifts could have strongly influenced in their results. Moreover, in contrast to our study, in which we assessed diet composition and other lifestyle outcomes such as physical activity and sleep habits showing no significant differences among both groups, they did not control any environmental factor that could also affect the gut microbial community.…”
Section: Resultsmentioning
confidence: 99%
“…78 Song et al reported improvements in GI side effects of amlodipine therapy with probiotics. 79 Amlodipine, as well as bacterial dysbiosis, has been associated with diarrhea.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%